EU Law on Public Finance Rules - Szegedi, László; Teleki, Bálint (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter discusses the public finances of the European Union (EU). The first subchapter covers the history of the EU public finances, examining the basic regulatory framework pursuant to the Maastricht Treaty and the Stability and Growth Pact and analysing in detail the connection with the 2008 crisis and its aftermath. The most important developments in the control over EU public finances are also discussed in this subchapter. The second subchapter introduces a critical approach to the current framework of the EU public finances, exploring the impact of the Stability and Growth Pact and its reforms, and discussing the possibility of the establishment of an Economic and Monetary Union 2.0 from multiple perspectives. The third subchapter focuses on contemporary challenges, in particular the COVID-19 pandemic and its impacts, as well as the effects of climate change and digitalisation on EU public finances.Keywords: 2008 financial-economic crisis, 2021-2027 Multiannual Financial Framework, climate finance, digital finance, Economic and Monetary Union 2.0, European Central Bank, European Commission, NextGenerationEU, Recovery and Resilience Facility, Stability and Growth Pact